Effect of Whole Wheat (Triticum aestivum) Feeding on the Performance of Commercial Broilers - Bhagora, Nikesh J.; Savaliya, Fulabhai P.; Patel, Atul B.; Patel, Dilip C. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was conducted for six weeks to study the effect of mixed or choice feeding of whole wheat on the performance of commercial broiler chicken. A total of 352 straight-run day-old commercial broiler chickens were randomly divided into 11 treatments from T1 to T11, with 32 chicks in each treatment and eight chicks in each of four replicates. The corn soya control diet (T1) was fed to the broiler birds without the inclusion of wheat. Results indicated that final body weight, weight gain, and FCR were significantly (p < 0.05) improved in broiler birds fed with 40% choice feeding of wheat at marketing age without affecting feed consumption. The wheat consumption was linearly increased in the wheat choice feeding levels from 20 to 100 %. The study concluded that the choice feeding of wheat instead of maize at 40% was cost-effective and beneficial for improving growth performance.
Keywords: Choice feeding; Commercial broilers; Economics,; Mixed feeding; Production performance; Whole wheat